The singing bones : inspired by Grimms' fairy tales - Tan, Shaun (Arthur A. Levine Books, an imprint of Scholastic Inc., 2016)
Selection and adaptation of seventy-five Grimm's fairy tales, as translated by Jack Zipes, and newly illustrated by Shaun Tan.